IDENTIFY AND PRIORITIZE FACTORS INFLUENCING THE REDUCTION OF ENGINEERING CANDIDATES FROM THE PERSPECTIVE OF 12th GRADE STUDENTS (CASE STUDY: ZAHEDAN CITY) - F. Mirshekari; M. R. Shahraki (آموزش مهندسی ایران, 2023)
Candidates for admission to engineering are graduates of mathematical physics. In the past few years, the number of students in mathematical physics has decreased sharply, which has reduced the number and quality of volunteers studying engineering in universities. This can have negative effects on the scientific and economic development of the country. In this study, first the Delphi method was used to identify factors that contribute to the decline of candidates studying engineering, based on the background of research and interviews. The second step was to prioritize these factors using the combined Dimatel approach and the network analysis process. The results of the study showed that the factors of education, future job opportunities, ability and interests of the person, family and parental opinion, and social and cultural, respectively, have the greatest interaction and communication with other factors. The results of the study of the criteria of factors also showed that the criteria for the existence of a greater perception of difficulty in studying and working in engineering disciplines, studying family members in other disciplines, the position and social status of studying in engineering disciplines are the most important among all the criteria that affect the reduction of candidates in engineering disciplines.